STRATEGI KOMUNIKASI PEMASARAN UNTUK MENINGKATKAN DAYA BELI KONSUMEN MELALUI MEDIA SOSIAL - Nurul Aini Safitri (Universitas Trunojoyo Madura, 2017)
Currently social media has an important role in promotional activities, is due to social media is the Internet activity with the most visitors, be it facebook, instagram, phatt, etc .. Therefore, the company began to enter the media to play an important role in promotional activities of a product by involving some nitizen as the owner of the account and make it as Resseler. The main task of a Resseler is to promote products and find customers. The income of a Resseler depends on the cost of the customer and the agreed price. There is no target set by the company, so that Resseler for an onlineshop is in great demand by all circles.